PENGARUH KOMITMEN ANGGARAN DAN INTENSITAS MORAL TERHADAP KECENDERUNGAN MENJADI WHISTLEBLOWER DENGAN GAYA KEPEMIMPINAN SEBAGAI PEMODERASI (STUDI PADA PEMERINTAHAN KABUPATEN ACEH JAYA) - Nalita, Farra; Adnan, Adnan (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This study aims to determine whether there is an effect of budget commitment and moral intensity on the tendency to become a whistleblower with leadership style as a moderating variable. The research respondents were 97 people, namely SKPK Aceh Jaya employees. Data collection was carried out by distributing questionnaires directly or through the respondent community at the end of February to mid-March 2022. This study was taken using a probability sampling technique, namely simple random sampling where the sample was taken randomly. The analytical method used is multiple linear regression with SPSS version 26 application. The behavior of a whistleblower is in line with the theory used in this study, namely prosocial behavior theory where behavior is mutually beneficial and useful for others. Meanwhile, budget commitment, moral intensity and leadership style are in line with the theory of planned behavior where intentions will affect the behavior or actions they take. The results of the study prove that budget commitment and moral intensity have a significant positive effect on the tendency to become whistleblowers in SKPK Aceh Jaya employees. Another result is that leadership style does not moderate the relationship between budget commitment and whistleblowers, but leadership style does moderate the relationship between moral intensity and whistleblowers. In the classification of moderating variables, the relationship between budget commitments and whistleblowers is called non-moderation, while the relationship between moral intensity and whistleblowers is called pure moderator.